2020
DOI: 10.3390/ijerph17238721
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Needlestick and Sharps Injuries When Using Devices with and without Safety Features

Abstract: Safety-engineered devices (SEDs) have been developed to protect healthcare personnel (HCP) from needlestick and sharps injuries (NSIs). The aim of this study was to analyze NSIs associated with SEDs and non-SEDs among HCP in hospitals, medical offices and care facilities. Records from online questionnaires on NSIs were used. Causes of NSIs were compared for SED use and healthcare setting. A sample of 835 files was included. Injuries with SEDs accounted for 35.0% of all NSIs, whereas the proportions were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Nurses reported total replacement in nearly 50% of cases in both surveys; in 2021, RSPP reported total replacement almost in 60% of cases, but pharmacists (in charge of purchasing devices) only in 31%. As in other European studies [ 41 ], costs were identified as one of the main reasons for not replacing conventional devices, but in 2021, pharmacists and RSPP indicated also difficulties in ordering safety devices. Device purchases are currently made through regional tenders, and safety features may not be included, or not be prioritized, within the required characteristics of the device, depending on the choices of the committee developing the tender.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Nurses reported total replacement in nearly 50% of cases in both surveys; in 2021, RSPP reported total replacement almost in 60% of cases, but pharmacists (in charge of purchasing devices) only in 31%. As in other European studies [ 41 ], costs were identified as one of the main reasons for not replacing conventional devices, but in 2021, pharmacists and RSPP indicated also difficulties in ordering safety devices. Device purchases are currently made through regional tenders, and safety features may not be included, or not be prioritized, within the required characteristics of the device, depending on the choices of the committee developing the tender.…”
Section: Discussionmentioning
confidence: 76%
“…The sore point is that, in none of these investigations, there was a total replacement of conventional devices with their safety counterpart: in 2013, the SIROH hospitals reported a total replacement in 70% of cases; in 17% it was total for some devices and partial for others, and in 13% only partial for all safety devices [ 27 ]. Although the effectiveness of safety devices is variable [ 36 ], as reported also in a Cochrane review [ 37 ], several studies report positive results regarding the ability of SED to reduce the number of percutaneous accidents [ 13 , 38 , 39 ]; the contemporary use of conventional, non-safety devices and SED is not beneficial [ 40 , 41 ]. Nurses reported total replacement in nearly 50% of cases in both surveys; in 2021, RSPP reported total replacement almost in 60% of cases, but pharmacists (in charge of purchasing devices) only in 31%.…”
Section: Discussionmentioning
confidence: 99%
“…NSIs among Italian and German physicians were more correlated with conventional sharps, whereas in nurses, NSIs were more correlated with SEMDs. [24][25][26] Further study is needed to understand the usage rates of SEMDs based on occupation, which can lead to improved preventive strategies against NSIs in higher-incidence groups.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a 2017 survey of perioperative nurse perception of teamwork performance and mental stress in Japan showed that 38 (30.6%) of 124 RN circulators experienced mental stress during procedures 18 . Findings from a 2020 study on the causes of needlestick and sharps injuries showed that a variety of factors contributed to such injuries for hospital HCWs, including stress, not paying attention, and device failure 19 …”
Section: Causes Of Perioperative Needlesticksmentioning
confidence: 99%
“…18 Findings from a 2020 study on the causes of needlestick and sharps injuries showed that a variety of factors contributed to such injuries for hospital HCWs, including stress, not paying attention, and device failure. 19…”
Section: Preventing Perioperative Sharps Injuriesmentioning
confidence: 99%